Analisis Potensi Mata Air Karst Untuk Kebutuhan Air Domestik Penduduk Desa Basuhan Kecamatan Eromoko Kabupaten Wonogiri - Syahidin, Umar; , Dra. Alif Noor Anna, M.Si; , Drs. Munawar Cholil, M.Si (2016)
This research was conducted in Karst regions with the title Analysis of potential springs Karst to meet the water needs of the domestic population karst village Basuhann Eromoko District of Wonogiri. The purpose of this study was to (1) analyze potential differences in the quantity and quality of water sources during the rainy season and dry season. (2) Comparing the daily domestic water needs with the potential availability of water springs population during the rainy season and dry season.This study used survey method and analysis laboratory. The analysis results are used in a descriptive study comparing the results of comparative means the quantity of springs that are there with the number of daily domestic water needs and further analyzing the quality of the springs with water quality standards.The results showed that the total discharge of springs in the dry season which is 1.67 liters / sec with a total volume of 144.288 liters of water / day and during the rainy season total debit of 5.3 liters / sec with a total volume of 4 57.920 liters of water / day. The mean amount of water consumption of the population in the study area during the dry season amounted to 66.37 liters / person / day and the rainy season amounted to 102.68 liters / person / day.Generally, the condition springs from laboratory results of physical properties (smell, taste, color, temperature, total dissolved solids, turbidity) and crime ( Ph, CacO3, KmNo4 , Cl ) still the standard in water quality standard. For bacteria exceeded the water quality standard for dringking.